Nebular thermal processing of accretionary fine-grained rims in the Paris CM chondrite. (15th February 2021) - Zanetta, P-M.; Leroux, H.; Le Guillou, C.; Zanda, B.; Hewins, R.H.
Highlights: Fine-grained rims are less altered than the matrix in the Paris chondrite. Matrix and fine-grained rims remain chemically similar. Fine-grained rims exhibit a radial evolution of porosity, texture and mineralogy. Fine-grained rims micro-texture evidence a pre-accretionary thermal episode. Matrix is accreted later in a colder and water-rich environment. Abstract: Fine-grained rims (FGRs) are ubiquitous in chondrites. They consist of unequilibrated mineral assemblages that surround chondrules and refractory inclusions. As such, they carry information about the material that was accreted onto chondrules. To decipher the nature and the formation mechanism of FGRs and compare them to adjacent matrix material, we investigated their composition, mineralogy, density and texture in the pristine Paris CM chondrite. We coupled a new method at the SEM scale (ACADEMY) that allows high-resolution quantitative petrology and an analytical TEM study. Significant differences in modal abundance, grain size and porosity are observed between the FGRs and their adjacent matrix. Amorphous silicates domains embedding nanosulfides are indicative of a high preservation degree. They are less abundant in the matrix than in the rims. In contrast, secondary alteration phases (phyllosilicates, carbonates and tochilinites) are more abundant in the matrix and associated with larger and fewer sulfides grains. The similar composition of the amorphous silicate in the rims and the matrix attests for a close relationship between the two reservoirs. However, matrix underwent more aqueous alteration. We interpret it as the result of the accretion of material with a higher water/rock ratio in the matrix, leading to a more aqueously altered microenvironment. We also find that coarse-grained anhydrous silicates (olivine and pyroxene) are present in the matrix but not in the FGRs, likely as a result of a chondrule fragmentation episode that occurred after FGR but before matrix accretion. Most of the time, FGRs display distinct inner and outer layers. The inner part is compact and displays larger sulfide grains than the outer part, which is more porous (porosity ∼ 45%) and altogether more pristine. These mineral and textural differences are not easily explained by differential aqueous alteration. Instead, a pre-accretion thermal process that preferentially affected the inner rim could have induced loss of porosity, compaction of the amorphous silicate domains as well as sulfides growth. We therefore suggest that FGRs acquired their characteristics in the nebula before matrix accretion and discuss possible mechanisms such as dust heating in the chondrule formation environment or secondary heating episode of the previously rimmed chondrule.